Supporting Black, Indigenous, and Students of Color in Learning Environments Transformed by COVID-19 - Mize, Min; Glover, Crystal (International Journal of Multicultural Education, 2021)
This article sheds light on the challenges that Black, Indigenous, and students of color in the U.S. face in dealing with uncertainties and prejudice caused by the worldwide pandemic. It provides recommendations on culturally relevant, responsive, and sustaining teaching strategies based on the cultural competence model (Pedersen, 1994; Sue, 2001; Sue et al., 1992;) and curriculum reframing. Teachers of Black, Indigenous, and students of color around the world will find this article particularly useful because there are limited research-based recommendations applicable to schools in the U.S. and around the world.